Pengaruh Penggunaan Bahasa Intimidasi pada Anak di Media Sosial Instagram - Malikha, Usrin (Universitas Al-Qolam Malang, 2025)
This study aims to analyze the impact of the use of intimidation language on children on the social media platform Instagram. Social media, particularly Instagram, has become one of the most popular platforms among teenagers and children. In the interactions that occur on this platform, the use of intimidation language often emerges, whether in the form of comments, direct messages, or posts. The intimidation language used can have negative effects on the psychological and emotional development of children. This study employs a quantitative approach with survey and interview methods to collect data from children who actively use Instagram. The results of the study indicate that the use of intimidation language has a significant impact on the psychological condition of children, reflected in increased anxiety, depression, and decreased self-esteem. Therefore, it is important for parents, educators, and social media platform administrators to raise awareness about the dangers of intimidation language and develop mechanisms to minimize its impact on children.